Respectful Maternity Care. Issue 4 (July 2022) - Bernstein, Samantha L.
Abstract : The Association of Women's Health, Neonatal, and Obstetric Nurses has published a new evidence-based clinical practice guideline on respectful maternity care. Our maternity nursing expert, Dr. Bernstein, summarizes the guideline and offers suggestions on how to apply the information to clinical practice. We welcome Dr. Bernstein as a regular contributor to the Hot Topics in Maternity Nursing column and to the MCN Editorial Board.